Perbedaan Pengaruh Dosis High Intensity Interval Training 1 Kali Seminggu dengan 2 Kali Seminggu terhadap Peningkatan Vo2 Max pada Mahasiswa - Fawaz Hibatullah, Hanan; Kusumaningtyas, Mei; Putri Nur Hidayati, Nitaya (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Cardiovascular fitness is a crucial aspect of student health, especially after the COVID-19 pandemic, which led to reduced physical activity. One proven method to enhance cardiovascular fitness is High-Intensity Interval Training (HIIT). However, there are differing opinions regarding the minimal HIIT dosage required to improve VO2 max. Objectives: This study aims to compare the effects of performing HIIT once a week versus twice a week on increasing VO2 max in students. Methods: This study employed a two-group pre-test and post-test design with a sample of 30 students who were randomly assigned into two groups. The first group performed HIIT once per week, while the second group performed HIIT twice per week for three consecutive weeks. VO2 max was measured before and after the intervention using the Beep Test. Results: The findings revealed that both groups experienced an increase in VO2 max after the intervention. In the once-per-week HIIT group, the average VO2 max increased from 32.60 ± 1.54 mL/kg/min to 32.75 ± 1.58 mL/kg/min, but the increase was not statistically significant (p > 0.05). In contrast, the twice-per-week HIIT group showed a more significant increase, from 31.58 ± 0.75 mL/kg/min to 32.16 ± 0.84 mL/kg/min (p < 0.05). Conclusion: Performing HIIT twice a week is more effective in improving VO2 max than performing it once a week. Keywords: High-Intensity Interval Training, VO2 max, cardiovascular fitness, students.